2020
DOI: 10.1007/s00262-020-02566-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryoablation combined with transarterial infusion of pembrolizumab (CATAP) for liver metastases of melanoma: an ambispective, proof-of-concept cohort study

Abstract: Background The presence of liver metastasis correlates with poor therapeutic response of PD-1 blockade therapy in melanoma. A novel treatment protocol by combining cryoablation with transarterial infusion of pembrolizumab (CATAP) was proposed, and its feasibility and safety was assessed among this group of patients. Methods This registered ambispective cohort study enrolled fifteen melanoma patients with multiple hepatic metastases who received planned two-stage CATAP therapy: in the combined stage, subtotal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Notably, the transarterial infusion of a pembrolizumab interval combined with the intravenous use of doxorubicin and carboplatin was effective in addressing immune resistance when disease progression occurred again after nearly 9 months of pembrolizumab monotherapy. According to previous studies of arterial infusion chemotherapy for ovarian cancer (29) and transarterial infusion of pembrolizumab for liver metastases of melanoma (30), the intra-arterial administration of pembrolizumab offers a much higher local drug concentration than the intravenous administration. Additionally, the immunostimulatory effects of chemotherapeutic drugs have already been proven to activate effector cells and/or inhibit immunosuppressive cells or enhance immunogenicity and improve the infiltration of lymphocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the transarterial infusion of a pembrolizumab interval combined with the intravenous use of doxorubicin and carboplatin was effective in addressing immune resistance when disease progression occurred again after nearly 9 months of pembrolizumab monotherapy. According to previous studies of arterial infusion chemotherapy for ovarian cancer (29) and transarterial infusion of pembrolizumab for liver metastases of melanoma (30), the intra-arterial administration of pembrolizumab offers a much higher local drug concentration than the intravenous administration. Additionally, the immunostimulatory effects of chemotherapeutic drugs have already been proven to activate effector cells and/or inhibit immunosuppressive cells or enhance immunogenicity and improve the infiltration of lymphocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of malignancies, decreasing tumor burden through cytoreductive cryoablation can have positive effect on survival. In particular, studies have demonstrated that cryoablation leads to better survival in patients with metastatic hepatocellular carcinoma ( 22 ), lung cancer ( 23 ), and melanoma ( 24 ), on top of strengthening tumor response to systemic therapy. Several studies have reported synergies between cryoablation and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, cryoablation combined with a transarterial infusion of pembrolizumab has shown promising clinical activity in managing melanoma liver metastasis. However, the efficacy of the therapy needs to be confirmed with a controlled trial in the future [ 186 ]. ROS production can be anticipated with this destructive modality, but the therapeutic relevance for cryoablation-related ROS in melanoma remains limited as of now.…”
Section: Ros In Melanoma Therapy With Physical Modalitiesmentioning
confidence: 99%